2016
DOI: 10.1002/ejhf.563
|View full text |Cite
|
Sign up to set email alerts
|

New York Heart Association functional class, QRS duration, and survival in heart failure with reduced ejection fraction: implications for cardiac resychronization therapy

Abstract: In HF with reduced LVEF, QRS prolongation is common and independently linked to worse survival. The increase in mortality risk associated with QRS prolongation of both LBBB and non-LBBB morphology is similar in NYHA class II and III-IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
2
26
0
1
Order By: Relevance
“…The Institutes of Medicine has identified implementation of safe and effective interventions into broad clinical practice as a major area needing improvement . We have previously described that as many as 30% of HFrEF patients may have indication for CRT, and that wide QRS and LBBB are associated with increased mortality consistently across varying demographics and independently of extensive baseline covariates …”
Section: Introductionmentioning
confidence: 99%
“…The Institutes of Medicine has identified implementation of safe and effective interventions into broad clinical practice as a major area needing improvement . We have previously described that as many as 30% of HFrEF patients may have indication for CRT, and that wide QRS and LBBB are associated with increased mortality consistently across varying demographics and independently of extensive baseline covariates …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the 1-year survival rate without CRT was 50-70% in ambulatory classes III-IV HF patients with QRS widening (≥120 ms, n = 2720) from the Swedish Heart Failure Registry. 22 Patients with QRS widening or dependency on IVDs/ISTs, like our patients, usually experience a worse prognosis than those without. 23,24 Outcomes of cardiac resynchronization therapy for intravenous drug/invasive supportive treatment-dependent far-advanced New York Heart Association class-IV heart failure patients…”
Section: Prognosis Of Ambulatory New York Heart Association Class-iv mentioning
confidence: 58%
“…Symptoms, assessed by NYHA class and QRS duration, but not QRS morphology, had an independent association with mortality in a large Swedish registry including 13 423 patients . Retrospective analyses of randomized trials have shown the independent prognostic value of both QRS duration and QRS morphology .…”
Section: Devices: Prognostic Determinants and Innovative Approachesmentioning
confidence: 99%